2008
DOI: 10.1159/000143221
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia versus Oral Controlled-Release Oxycodone – Are They Interchangeable for Acute Postoperative Pain after Laparoscopic Colorectal Surgeries?

Abstract: Background: Standard therapy for postoperative pain after laparoscopic colorectal surgeries at the Tan Tock Seng Hospital consists of intravenous morphine via patient-controlled analgesia (PCA) for the first 24–48 h, followed by oral analgesics. We compared the efficacy and safety of oral controlled-release (CR) oxycodone hydrochloride (OxyContin® tablets) and PCA after laparoscopic colorectal surgeries. Methods: Between March and August 2006 (phase 1 study), 14 patients underwent laparoscopic colectomy, lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Given that intrathecally administered morphine is more effective than intravenous morphine for postcaesarean pain relief (46), oral oxycodone appears to offer satisfactory analgesia in this pain setting. In postsurgical situations involving colorectal (25) and cardiac surgeries (20), the analgesic quality of oral oxycodone was comparable to intravenous morphine.…”
Section: Postsurgical Analgesic Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that intrathecally administered morphine is more effective than intravenous morphine for postcaesarean pain relief (46), oral oxycodone appears to offer satisfactory analgesia in this pain setting. In postsurgical situations involving colorectal (25) and cardiac surgeries (20), the analgesic quality of oral oxycodone was comparable to intravenous morphine.…”
Section: Postsurgical Analgesic Efficacymentioning
confidence: 99%
“…The authors suggested that sub-therapeutic plasma levels (mean Cmax 10.0 ng/ mL) of oxycodone found in the study participants could have contributed to the lack of analgesic efficacy. Ho (25) compared the efficacy and safety of CR oxycodone and intravenous PCA morphine following laparoscopic colorectal surgery. Patients in the oxycodone group received CR oxycodone 10 mg postoperatively upon return to the ward followed by 10 mg twice a day as needed.…”
Section: Se37mentioning
confidence: 99%
“…[67] Oral oxycodone was also reported to be a safe, effective, and cost-effective alternative to patient-controlled analgesia (PCA) systems using opioids for control of postoperative pain. [68] Oxycodone is available in intravenous, subcutaneous, intramuscular, and oral formulations. Route of administration may be an important consideration in prescribing: intravenous drugs are more expensive and require hospitalization, while oral agents are generally more inexpensive and convenient.…”
Section: Selecting the Right Opioid: When Can Ir Oxycodone Be A Good mentioning
confidence: 99%
“…Opioids are required for optimal analgesia in most colorectal procedures, however oral administration has been shown to be sufficient in laparoscopic colorectal surgery [55]. Furthermore, oral opioid administration compared to patient-controlled analgesia is safe, cheaper, does not require patient-education, and does not reduce mobility of the patient.…”
Section: Multimodal Analgesic Treatmentmentioning
confidence: 99%